2013
DOI: 10.1007/s11695-013-0925-z
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study Comparing Patients with Morbid Obesity Submitted to Sleeve Gastrectomy With or Without Omentectomy

Abstract: The theoretical advantages of omentectomy in regard to weight loss and obesity-related abnormalities are not confirmed in this prospective study. Furthermore, omentectomy does not induce important changes in the inflammatory status in patients undergoing SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Besides the time and the own reduction of weight, the type of surgical technology can also influence. Sdralis et al [29] have reported that after 1 year postoperatively, omentin-1 levels increased significantly in the sleeve gastrectomy group and decreased in the omentectomy group.…”
Section: Discussionmentioning
confidence: 98%
“…Besides the time and the own reduction of weight, the type of surgical technology can also influence. Sdralis et al [29] have reported that after 1 year postoperatively, omentin-1 levels increased significantly in the sleeve gastrectomy group and decreased in the omentectomy group.…”
Section: Discussionmentioning
confidence: 98%
“…Sdralis et al [24] evaluated the impact of omentectomy in patients with morbid obesity undergoing sleeve gastrectomy (SG) on adipokine secretion. After 1 year postoperatively, omentin-1 levels increased significantly in the control group only with SG after a mean weight loss of 50 kg and decreased in the omentectomy group.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with interventional studies that involve removal of the omental depot in obese individuals. In eight out of nine published studies, addition of omentectomy to gastric bypass or sleeve gastrectomy did not augment weight loss or the improvement in insulin sensitivity and other metabolic indices achieved by the bariatric intervention itself (Table 2) [84-91]. Although longer-term follow-up and the incidence of cardiovascular events can be assessed in future studies, these data question the causative role of omental adipose tissue in metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%